Efisiensi Teknis Usahatani Bawang Merah di Kabupaten Nganjuk dengan Fungsi Produksi Cobb Douglass Stokastik Frontier - Hardianingsih, Yesi Dwi; Nugroho, Taufik Rizal Dwi Adi; Priyanto, Moh. Wahyudi (Journal of Agribusiness, Social and Economic, 2025)
This study aims to analyze the technical efficiency of shallot farming in Nganjuk Regency using the Cobb-Douglas Stochastic Frontier production function approach. The research was conducted in four sub-districts with a total of 130 farmer respondents. Sampling was carried out using the accidental sampling technique, and data were analyzed using the Maximum Likelihood Estimation (MLE) method. The results show that the technical efficiency of shallot farmers is relatively high, with an average score of 0.966, a maximum of 0.998, and a minimum of 0.901. The majority of farmers (98%) fall within the efficiency range of 0.91–1.00. Among the six input variables analyzed, three were found to significantly affect production: seed (0.298), land area (-0.066), and ZA fertilizer (-0.092). On the other hand, farmer age was found to increase technical inefficiency (0.004), while farming experience reduced inefficiency (-0.005). These findings indicate that improving efficiency can be achieved by optimizing input use and leveraging farmers' experience in managing agricultural practices more effectively.